Business Feasibility Study on Hydroponic Vegetable Business in Ciawi Bogor Area (Bogor Veggies Case Study) - Hardiansyah Hardiansyah; Desi Harsanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Hydroponic vegetables are vegetables that grow with the help of liquids that contain nutrients needed by vegetables to grow. Hydroponics uses water that is more efficient, so it is suitable to be applied in areas that have a limited water supply. The water used to grow these vegetables can also be recycled. Plants like this, healthier than using fertilizers, because without chemicals. Hydroponic vegetable plants, many people like to understand health, because it is considered healthier when compared to vegetable crop grown using fertilizer.The purpose of this study is to determine and analyze the feasibility of hydroponic vegetable business in the Ciawi Bogor region (Bogor Veggies Study Case) seen from non-financial aspects, namely market aspects, legal aspects, technical aspects and management aspects and financial aspects. So that the capital that has been invested in this business can be more effective and implementation and the output produced will be maximized.The data used in this study are primary data and secondary data. Data The primary is obtained by direct observation of only one business actor hydroponic vegetables in the Ciawi Bogor region (Bogor Veggies Case Study) the business actor has fulfilled the criteria determined as a business actor hydroponic vegetables in Bogor Regency. Secondary data obtained from financial reports and sales reports and literature relevant to research in the form of books, results of previous studies, and internet publicationsQualitative analysis is used to analyze the feasibility of non-financial aspects such as market aspects, legal aspects, technical aspects and management aspects. Quantitative Analysis used to analyze eligibility based on investment criteria. Financial aspects in Bogor Veggies business shows that the payback period is 1 years 4 months 1 days, NPV is Rp 126.869.865, IRR is 49 percent, and profitability index is 3,504 percent. The results of this feasibility analysis indicate that the hydroponic vegetable business in the Ciawi Bogor region is feasible based on market aspects, legal aspects, technical aspects, management aspects and financial aspects.